2021 IEEE International Conference on Multisensor Fusion and Integration for Intelligent Systems (MFI) 2021
DOI: 10.1109/mfi52462.2021.9591188
|View full text |Cite
|
Sign up to set email alerts
|

UKF Parameter Tuning for Local Variation Smoothing

Abstract: The unscented Kalman filter (UKF) is a method to solve nonlinear dynamic filtering problems, which internally uses the unscented transform (UT). The behavior of the UT is controlled by design parameters, seldom changed from the values suggested in early UT/UKF publications. Despite the knowledge that the UKF can perform poorly when the parameters are improperly chosen, there exist no wide spread intuitive guidelines for how to tune them. With an application relevant example, this paper shows that standard para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…First, we consider the parameters α and κ and their effect on the estimation of the mean. We will follow the guidelines that typically we would use the unscaled UT (α = 1 and κ > 0), but when necessary to decrease the spread of the sigma-points we would use the scaled UT with (κ = 0 and α < 1) 10 . 9 () gz ()…”
Section: Estimating the Mean With Ekf And Ukf After A Nonlinear Trans...mentioning
confidence: 99%
“…First, we consider the parameters α and κ and their effect on the estimation of the mean. We will follow the guidelines that typically we would use the unscaled UT (α = 1 and κ > 0), but when necessary to decrease the spread of the sigma-points we would use the scaled UT with (κ = 0 and α < 1) 10 . 9 () gz ()…”
Section: Estimating the Mean With Ekf And Ukf After A Nonlinear Trans...mentioning
confidence: 99%
“…In Nielsen et al (2021) it has been shown that the choice of these is problem-dependent and has a significant influence on the filter performance. However, for the scope of this paper, we choose α = 10 −3 , β = 2 and κ = 0.…”
Section: Square-root Unscented Kalman Filtermentioning
confidence: 99%
“…While the measurement covariance R ∈ R m×m often is easier to determine by taking a closer look at the plant's measurements, the initial square-root covariance S 0 and the process covariance Q ∈ R ñ×ñ remain a major challenge in filter design, see e.g. Chen et al (2021); Nielsen et al (2021). When promoting sparsity within the SQ-UKF even an additional covariance R pm ∈ R comes along which determines the pseudo measurements' performance.…”
Section: Curse Of Dimensionmentioning
confidence: 99%
“…In a similar vein, Theiler et al [32] used a multi-objective fitness function within the same framework, particularly targeting identification of states and parameters for lithium-ion batteries. As a more systematic approach, Scardua and Cruz [33,34] developed a surrogate model of the desired hyperparameters and tried to optimize the parameters by maximizing the probability of the measured data. In another approach, Graybill et al [35] defined a multi-objective loss function to find optimal hyperparameters that satisfy the desired objectives, such as optimizing computational time or specified error functions.…”
Section: Introductionmentioning
confidence: 99%